2019
DOI: 10.3892/ol.2019.10290
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer cells release high mobility group box 1 and promote the formation of neutrophil extracellular traps

Abstract: Lung cancer is the leading cause of cancer-associated mortality. Tumor-associated neutrophils represent a large portion of inflammatory cells within the lung tumor microenvironment. However, the roles of neutrophil extracellular traps (NETs) in lung cancer remain unclear. In the present study, it was identified that Lewis lung carcinoma cells actively released the danger-associated molecular pattern protein high mobility group box 1 (HMGB1). Furthermore, HMGB1 in lung cancer cell supernatants promoted the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…At various time points, supernatant from each well was harvested, and extracellular DNA was quantified by adding the live cell-impermeable DNA dye Sytox Green (1 μM; S11368, Thermo) and examining the fluorescence intensity with Synergy HTX at an excitation wavelength of 488 nm and an emission wavelength of 523 nm (ref. 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At various time points, supernatant from each well was harvested, and extracellular DNA was quantified by adding the live cell-impermeable DNA dye Sytox Green (1 μM; S11368, Thermo) and examining the fluorescence intensity with Synergy HTX at an excitation wavelength of 488 nm and an emission wavelength of 523 nm (ref. 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Neutrophil extracellular traps (NETs), extracellular fibers composed of DNA, and granular enzymes, were once considered a weapon of neutrophils for trapping and killing microbes 9 . In addition to pathogen components, endogenous danger-associated molecular patterns, including high-mobility group box 1 (HMGB1) from injured tissues 10 or cancer cells 11 , may also trigger the production of NETs. Ongoing efforts have expanded the roles of NETs into diverse diseases, including autoimmune diseases 12 , pulmonary diseases 13 , and cancer metastasis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…NETs were initially thought to be a mechanism by which neutrophils clear pathogens, for example, the replication of staphylococcus aureus, salmonella typhimurium, streptococcus pneumoniae, and shigella flexneri can be inhibited by NETs 30 , 33 - 35 . But its critical role in sterile inflammation has also been revealed in recent years, such as deep venous thrombosis 36 , lung cancer 37 , arthritis 38 , AP 25 , 39 , 40 , endogenous particulate-related injury 41 , glioma 31 , liver ischemia-reperfusion injury 42 , ischemic stroke 43 , etc.…”
Section: Neutrophilsmentioning
confidence: 99%
“…Although some findings have been obtained, there is no consensus regarding this issue. A previous study revealed that NETs were produced by neutrophils in a toll-like receptor 4 (TLR4) and high-mobility group box 1 (HMGB1)-dependent manner in lung cancer cells ( 92 ). In addition, it has also been reported that the chronically inflammatory microenvironment contributes to the formation of NETs via an MPO–NETs–antineutrophil antibody (ANCA) axis in cancer ( 93 , 94 ).…”
Section: Part Ii: Nets In Cancermentioning
confidence: 99%
“…Regarding therapeutic targets related to NETs in lung cancer, it was previously revealed that the DAMP protein HMGB1 released by lung cancer cells contributes to the induction of NETs that was dependent on the activation of TLR4 ( 92 ). In addition, extracellular RNAs (exRNAs) produced by lung cancer cells have also been demonstrated to induce NET formation, which promotes cancer cell proliferation and migration ( 143 ).…”
Section: Part Iii: Nets In Different Types Of Cancermentioning
confidence: 99%